Current Understanding on Antihepatocarcinoma Effects of Xiao Chai Hu Tang and Its Constituents. (18th June 2013) - Zheng, Ningning; Dai, Jianye; Cao, Huijuan; Sun, Shujun; Fang, Junwei; Li, Qianhua; Su, Shibing; Zhang, Yongyu; Qiu, Mingfeng; Huang, Shuang
Abstract : Xiao Chai Hu Tang (XCHT), a compound formula originally recorded in an ancient Chinese medical book Shanghanlun, has been used to treat chronic liver diseases for a long period of time in China. Although extensive studies have been demonstrated the efficacy of this formula to treat chronic hepatitis, hepatic fibrosis, and hepatocarcinoma, how it works against these diseases still awaits full understanding. Here, we firstly present an overview arranging from the entire formula to mechanism studies of single herb in XCHT and their active components, from a new perspective of "separation study, " and we tried our best to both detailedly and systematically organize the antihepatocarcinoma effects of it, hoping that the review will facilitate the strive on elucidating how XCHT elicits its antihepatocarcinoma role.